A Psychological Approach to Analyzing Moral Values and Dominance in Migration (2023) - Afifah, Edsa; Prastiwi, Yeny (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
This study analyzes the moral values and the dominant moral value portrayed in the animated film Migration, directed by Benjamin Renner and produced by Illumination. As animated films increasingly function as media for moral education, examining their ethical messages becomes important. Previous studies on moral values in animated films mainly applied descriptive and semiotic approaches, focusing on visible moral messages rather than the psychological processes behind characters’ moral reasoning. To address this gap, this research employs a psychological approach using Sigmund Freud’s structural model of Id, Ego, and Superego, Lawrence Kohlberg’s stages of moral development, and the moral value framework proposed by Linda Eyre and Richard Eyre. This study uses a qualitative descriptive design with data collected from dialogues, character actions, and narrative scenes. The findings reveal eleven moral values categorized into values of being and values of giving. Among these, bravery emerges as the most dominant moral value, highlighting courage and resilience as central themes of the narrative.